In vitro studies of hydrogels as cell carriers for human mesenchymal stem cells intended for transplantation into degenerated intervertebral discs - Hansson, Axelia; Wenger, Anna (My University, 2014)
Low back pain is a major public health issue in the western world, which afflicts 70-85% of all people at some point in their life, and the prevalence of low back pain is reported to be as high as 84%. One main cause of low back pain is believed to be degeneration of the intervertebral discs in the spine. Disc degeneration is a combination of increased cell death, presence of matrix degrading enzymes, lack of nutrient supply, loss of gel-like structure in the nucleus pulposus (located in the center of the disc), leading to tissue dehydration, reduced disc height and fissure formation. Current treatments for low back pain include physiotherapy and surgery, but they are not very effective and the surgical process of fusing vertebrae is very invasive. New treatments for halting or diminishing disc degeneration are therefore needed and transplantation of cells, so called cell therapy, has been suggested. Hydrogels as a cell carrier and the incorporation of growth factors have been proposed to improve the efficacy of reducing the disc degeneration. The idea is that the transplanted cells will repopulate the disc, differentiate into chondrocyte-like cells, which are similar to nucleus pulposus cells naturally present in the disc, and produce extracellular matrix. This will restore the gel-like properties of the nucleus pulposus and thus reverse the degeneration of the disc. This thesis work examined two hydrogels, Puramatrix and Hydromatrix, in vitro as cell carriers for human mesenchymal stem cells intended for transplantation into degenerated intervertebral discs. Mesenchymal stem cells and degenerated disc cells from three patients were seeded in the hydrogels and in pellet cultures (control system) and analyzed at day 7, 14 and 28. The properties of mesenchymal stem cells in the hydrogels were studied regarding their ability to attach as well as proliferate in the hydrogel, produce extracellular matrix and differentiate into chondrocyte-like cells. The methods used to examine these properties were mainly immunohistochemistry, RT-PCR and TUNEL assay, but methods including FACS, SEM and rheology measurements were also employed. The results showed that more than 90% of the cells cultured in Puramatrix and Hydromatrix were viable for at least 28 days (end point of experiment). Both mesenchymal stem cells and disc cells were shown with immunohistochemistry to express integrin β1 and attach to Puramatrix and Hydromatrix respectively. Both cell types were also observed to proliferate in Hydromatrix as seen by immunohistochemistry staining of PCNA. The growth hormone Genotropin increased the expression of PCNA by mesenchymal stem cells from all patients and might therefore increase the proliferation, but further studies are needed to verify this limited setup. Differentiation was not observed in this study for mesenchymal stem cells (from all patients) cultured in Puramatrix and in pellet culture, for the two oldest patients. Mesenchymal stem cells from all three patients differentiated into chondrocyte-like cells in Hydromatrix and in pellet culture for the youngest patient and produced extracellular matrix similar to cartilage. This was verified by expression on gene level and protein level by the chondrogenic markers Sox-9, collagen type II and the proteoglycan aggrecan. Chondrogenesis in Hydromatrix was, by some mechanism, up regulated in the hydrogel compared to the pellet control system, which showed decreasing chondrogenic potential with increasing donor age. We conclude that Hydromatrix is a promising cell carrier for chondrogenesis of mesenchymal stem cells and a candidate for regenerating degenerated discs.
Keywords: Energi; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Biologiska vetenskaper; Energy; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Biological Sciences